List of species records of enchytraeids (Enchytraeidae, Clitellata, Annelida) in China - Chen, Juanjuan; Zhang, Junqian; Xie, Zhicai (Zootaxa, 2025)
The enchytraeid fauna of China is reviewed based on published records and unpublished theses. According to the up-dated checklist, there are 106 species belonging to 21 genera. The enchytraeid fauna of China is characterized by a large number of endemic species: 46 species have been recorded only in China, accounting for almost half of the total number of species. The endemics include 18 species of Mesenchytraeus, 7 species of Fridericia, 4 species each of Marionina and Hemienchytraeus, 3 species each of Bryodrilus and Grania, 2 species each of Enchytraeus and Oconnorella, 1 species of Xetadrilus and two endemic genera, Sinenchytraeus and Isosetosa, each containing 1 species, the latter however with doubtful taxonomic status. New records are included as well, and 8 species are recorded for the first time from the country. We also provide comments on doubtful species records.